Synthetic and natural Peroxisome Proliferator-Activated Receptor (PPAR) agonists as candidates for the therapy of the metabolic syndrome - Tan, Chek Kun (2017)
INTRODUCTION: Peroxisome proliferator-activated receptors (PPARs) are the molecular targets of hypolipidemic and insulin-sensitizing drugs and implicated in a multitude of processes that fine-tune the functions of all organs in vertebrates. As transcription factors they sense endogenous and exogenous lipid signaling molecules and convert these signals into intricate gene responses that impact health and disease. The PPARs act as modulators of cellular, organ, and systemic processes, such as lipid and carbohydrate metabolism, making them valuable for understanding body homeostasis influenced by nutrition and exercise. Areas covered: This review concentrates on synthetic and natural PPAR ligands and how they have helped reveal many aspects of the transcriptional control of complex processes important in health. Expert opinion: The three PPARs have complementary roles in the fine-tuning of most fundamental body functions, especially energy metabolism. Understanding their inter-relatedness using ligands that simultaneously modulate the activity of more than one of these receptors is a major goal. This approach may provide essential knowledge for the development of dual or pan-PPAR agonists or antagonists as potential new health-promoting agents and for nutritional approaches to prevent metabolic diseases.